Zeke Meeks vs. the stinkin' science fair - Green, D. L. (Debra L.) (Zeke Meeks, 2012)
Third-grader Zeke Meeks needs to win the prize in the science project contest because the class bully is threatening him, but so far all his ideas are ending in messy disasters--can his friend Hector save the day?